STUDI LITERATUR ASPIRASI KARIR SISWA - Mita Lestari; Elni Yakub; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Career aspiration is something that must be owned by every individual, especially for students who are at the Middle and High School level. At this time, students begin to think about the career plans they want to choose for their future. However, not all students have a good level of career aspirations, some of them still do not know what type of career they want to choose in the future. Therefore, this study aims to determine the concepts and theories of students' career aspirations, the factors that influence students' career aspirations, as well as efforts to increase students' career aspirations. This research is a literature study of various existing research journals and reference books, with a range of years between 2015 and 2020. Then the data is packaged as data and information material that can provide an overview of students' career aspirations. The recapitulation results show that career aspirations are individual orientations towards career goals that are in accordance with the desired expectations, needs, motives, and desires of a person in a career. While the most widely used theory to explain the factors that influence students in determining careers is the theory of Krumboltz's Social Learning Society, where personality and environment become factors that determine student decision making or career determination. So the role of guidance and counseling teachers is very much needed in an effort to increase students' career aspirations through specialization programs and the implementation of career guidance services in schools.Key Words: Career aspiration, Student, Middle and High Schools, Guidance andCounseling Teacher.